2023
DOI: 10.1027/1016-9040/a000485
|View full text |Cite
|
Sign up to set email alerts
|

Dark Tetrad, Acceptance of Sexual Violence, and Sexism

Abstract: Abstract. The Dark Tetrad is a cluster of four “dark” personality traits which are socially aversive, with distinct conceptual roots, but which are intercorrelated: narcissism, psychopathy, Machiavellianism, and sadism. Narcissism is associated with inflated self-esteem and feelings of grandiosity; psychopathy involves reduced empathy and a lack of remorse or guilt; Machiavellianism is characterized by a tendency for manipulation for own personal benefit; sadism involves feelings of pleasure with the pain or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…Regarding narcissism specifically, Baumeister et al (2002) have proposed a narcissistic reactance theory of sexual assault, according to which the feelings of sexual entitlement lead the narcissistic individual, in the face of sexual denial, to feel highly rejected, to desire having sex more, and to try to reclaim it by forcing the person who has refused it. In line with this, the Dark Tetrad has also been linked with the acceptance of sexual violence (for a review, see Costa et al, 2023)-particularly in the form of rape myth acceptance (Boland, 2018;Costa, 2020;DeLisle et al, 2019;Jonason et al, 2017), with psychopathy having been found to be the only "dark" trait that emerges as a unique predictor of rape-enabling attitudes including rape myth acceptance (Jonason et al, 2017).…”
Section: The Dark Tetrad Sexual Violence and Machismomentioning
confidence: 93%
“…Regarding narcissism specifically, Baumeister et al (2002) have proposed a narcissistic reactance theory of sexual assault, according to which the feelings of sexual entitlement lead the narcissistic individual, in the face of sexual denial, to feel highly rejected, to desire having sex more, and to try to reclaim it by forcing the person who has refused it. In line with this, the Dark Tetrad has also been linked with the acceptance of sexual violence (for a review, see Costa et al, 2023)-particularly in the form of rape myth acceptance (Boland, 2018;Costa, 2020;DeLisle et al, 2019;Jonason et al, 2017), with psychopathy having been found to be the only "dark" trait that emerges as a unique predictor of rape-enabling attitudes including rape myth acceptance (Jonason et al, 2017).…”
Section: The Dark Tetrad Sexual Violence and Machismomentioning
confidence: 93%
“…For instance, research has found that a combination of psychopathic traits such as affective facets, but mostly antisociality, are related to sexual violence and sexual sadism 17 , 18 . Everyday sadism is regarded as a subclinical personality construct of enjoying cruelty, humiliation and violent behavior and taking pleasure from other people’s psychological or physical suffering 8 , 19 . Moreover, everyday sadism strongly predicts higher sexual drive 9 and is associated with increased engagement in harmful, sexually aggressive behaviors 16 , 20 .…”
Section: Dark Tetrad Personality Traits and Deviant Sexual Interests ...mentioning
confidence: 99%
“…Over the past several decades, a sizeable body of empirical research has related one or more Dark Tetrad traits to various harmful interpersonal outcomes (e.g., short-term relationships, aggression, infidelity), including indicators of sexual violence against women (Costa et al, 2022). Specifically, significant positive associations have been found between psychopathy dimensions (e.g., interpersonal, antisocial behavior) and RMA in samples of male prisoners and nonprisoners (Debowska et al, 2015) and college students (Mouilso & Calhoun, 2013).…”
mentioning
confidence: 99%